Exploring How Vaccine Information is Communicated in NSW Public Libraries: A Study on Perceptions and Practice. Issue 4 (2nd October 2022) - Wallace, Kayla Stephanie
ABSTRACT: With COVID-19's global impact and the increased demand for accurate, accessible vaccine messaging, public libraries – equipped with pre-existing infrastructure and trained information professionals – are uniquely positioned to address this need. However, studies have shown that these expectations rarely align with both past and current practice. This small exploratory study examines library practices alongside librarian perceptions in New South Wales, Australia with the goal of identifying whether they align and what key factors influence the communication of vaccine information. It reports on the findings of a three-strand investigation of library catalogues, websites, and interviews with current NSW public librarians. Ultimately, findings suggested that public libraries had taken few steps towards effectively communicating vaccine information during the early stages of the pandemic. While vaccine collections existed, they were limited in size, outdated, and predominantly print-based. Additionally, cataloguing practices made it difficult to discern anti-vaccine from pro-vaccine resources, while library websites offered minimal vaccine information and lacked accessibility for low literacy or non-English speaking users. These findings largely aligned with the perspectives of the interviewed librarians, who raised concerns regarding the size and accessibility of vaccine resource collections, the importance of expanding digital resources, and improving the communication of vaccine information.